2017
DOI: 10.17691/stm2017.9.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Reconstruction of Main Arteries by Perivascular Implantation of Sulfated Chitosan in Experimental Atherosclerosis

Abstract: The aim of the study is to demonstrate morphological reconstruction of the main arteries of rabbit hind limbs by perivascular implantation of sulfated chitosan in an atherosclerosis model.Materials and Methods. The study was performed on 24 rabbits divided into four groups of 6 animals. The rabbits in the experimental group kept on intensive cholesterol diet for 110 days were implanted 1% water-soluble sulfated chitosan gel in the perivascular fascial compartment of the saphenous artery and the femoral artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The dislocation of sulfated chitosan near cell membranes in the subintimal region suggests its active interaction with cholesterol in macrophages, its binding to extracellular and intracellular cholesterol, and transport of its water-soluble electrolyte complex with lipid mass [61] into the para-adventitial region in the composition of chitosan nuclei [60]. It is assumed that the targeted transport of lipid fractions occurs due to an electrostatic gradient [64][65][66], which is caused by artificial minimally invasive dislocation of chitosan [47] in the fascial sheath of large vessels. Our study convincingly shows the local release of cholesterol and low-density lipoproteins from the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dislocation of sulfated chitosan near cell membranes in the subintimal region suggests its active interaction with cholesterol in macrophages, its binding to extracellular and intracellular cholesterol, and transport of its water-soluble electrolyte complex with lipid mass [61] into the para-adventitial region in the composition of chitosan nuclei [60]. It is assumed that the targeted transport of lipid fractions occurs due to an electrostatic gradient [64][65][66], which is caused by artificial minimally invasive dislocation of chitosan [47] in the fascial sheath of large vessels. Our study convincingly shows the local release of cholesterol and low-density lipoproteins from the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…This flow outside the outer shell of the vessel can be provided by an electrostatic gradient, which is created due to the polycationic properties of chitosan [60,64]. Artificial minimally invasive dislocation of chitosan nanoparticles in the fascial sheath of the main vessels provides this gradient [65,66] and can be designed for the directed flow of the lipid mass towards the adventitia.…”
Section: Mechanisms Of Formation Of Vascular Atherosclerosis and Sign...mentioning
confidence: 99%
“…Chitoheptaose was also proven in an experiment to obtain oxidant, inflammatory, and apoptotic resistance so that it could defend the heart in a model of myocarditis ( 58 ). Recent studies indicated that if chitosan sulfate was embedded into the perivascular chamber, remedial angiogenesis could be achieved to restrain the initial indication of atherosclerotic inflammation ( 59 ).…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Li et al conjugated hydroxybutyl chitosan (HBC) to anti-CD133 antibody to prepare a CD133 antibody-coated stent, which has shown the ability to decrease intimal hyperplasia and reduce restenosis in contrast with bare stents, which suggests that the stents of the CD133 antibody coat may contribute to the treatment of AS [116]. In addition, implantation of sulfated chitosan into the perivascular compartment achieves therapeutic paravasal angiogenesis and inhibits the early signs of atherogenic inflammation [117]. These studies provide new research directions and treatment ideas for AS and stimulate further development of chitosan and its derivatives in this field.…”
Section: Chitosanmentioning
confidence: 99%